3D reconstruction for damaged documents: Imaging of the great parchment book - Pal, Kazim; Terras, Melissa; Weyrich, Tim (ACM International Conference Proceeding Series, 2013)
Digitization of historical documents is extremely useful as it allows easy access to the documents from remote locations and removes the need for potentially harmful physical handling. Traditional imaging methods are unsuitable for documents with complex geometry as they will produce images containing perspective distortions, and 3D imaging methods previously proposed for document scanning will often suffer from occlusions and/or require manual alignment of individual range scans. We present a lightweight pipeline for imaging and generating 3D reconstructions of severely damaged and distorted documents which exhibit such complex geometry. We demonstrate our pipeline on The Great Parchment Book of The Honourable The Irish Society, a 17th century survey of the Ulster estates managed by the City of London, which was severely damaged by a fire in 1786. Copyright 2013 ACM.
CRIS-Team Scopus Importer:2022-07-26
Keywords: 3D reconstruction; Document digitisation; Scanning